Therapeutic Communication Skills of Nursing Students in Clinical Practice - Darmi Arda; Suprapto Suprapto (LPPM Politeknik Sandi Karsa, South Sulawesi, Indonesia, 2023)
Communication in nursing is called therapeutic communication, which is a way of fostering a therapeutic relationship between nurses and patients that has the aim of helping in the patient's healing process. This study aims to determine therapeutic communication skills for nursing students in clinical practice. The type and design used in this study is quantitative research. Fisher's Exact Test results obtained p-value (0.000) < α value (0.05). It can be concluded that there is a relationship between knowledge and therapeutic communication skills in the clinical practice of nursing students. Therapeutic knowledge and communication skills are essential in the clinical practice of student nursing. Medicinal communication knowledge and skills are critical elements in a student's nursing clinical practice. This is at the core of effective and empathetic patient care